1974
DOI: 10.1111/j.1469-1809.1974.tb01992.x
|View full text |Cite
|
Sign up to set email alerts
|

The genetics of the Lp Antigen

Abstract: SUMMARY Several genetic models were considered to explain the distribution of qualitatively positive and negative children in 204 Caucasian families. A model which best describes the inheritance of the Lp antigenic expression involves a major genetic locus which distinguishes two overlapping continuously distributed modes of quantitative activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

1983
1983
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…The concordance of Lp(a) levels among siblings with the apo(a) genotype suggest that factors at the apo(a) locus than number ofkringle 4 repeats are contributing to the pl; Lp(a) level. (27,28 After the original suggestion of Utermann and co-workers (12), several investigators have noted an inverse relationship between the size of the apo(a) protein and the amount of plasma Lp(a) (13,16,30 (22,(50)(51)(52)(53). A problem which has been encountered when the apo(a) protein have been used for segregation analysis, is that the isoforms are not in Hardy-Weinberg equilibrium (12)(13)(14)(15)(16).…”
Section: Resultsmentioning
confidence: 99%
“…The concordance of Lp(a) levels among siblings with the apo(a) genotype suggest that factors at the apo(a) locus than number ofkringle 4 repeats are contributing to the pl; Lp(a) level. (27,28 After the original suggestion of Utermann and co-workers (12), several investigators have noted an inverse relationship between the size of the apo(a) protein and the amount of plasma Lp(a) (13,16,30 (22,(50)(51)(52)(53). A problem which has been encountered when the apo(a) protein have been used for segregation analysis, is that the isoforms are not in Hardy-Weinberg equilibrium (12)(13)(14)(15)(16).…”
Section: Resultsmentioning
confidence: 99%
“…The Lp(a) lipoprotein exhibits a quantitative genetic polymorphism (28,29) and the Lp(a) specific glycoprotein (apo (a)) shows a qualitative genetic polymorphism (21). 14 of the 18 patients showed significant changes (defined as at least twofold) in Lp(a) lipoprotein plasma concentration (Table III).…”
Section: Resultsmentioning
confidence: 99%
“…>30 mg/dl is considered to be genetically or racially determined [6], the level is often found to be higher in patients with IDDM than in healthy control subjects as reported by Rudberg and Persson [7]. They concluded that Lp(a) was elevated during puberty in normoalbuminuric subjects with IDDM, independent of metabolic control and IGF-I.…”
Section: Introductionmentioning
confidence: 90%